Poligami dalam Pemikiran K.H. Hussein Muhammad - Zulfikri, Zulfikri; Nurhidayatullah, Ahmad Syawal (Institut Agama Islam Negeri Kerinci, 2023)
When viewed from a historical perspective, marriage existed and was carried out before the arrival of Islam. However, it is known that marriages carried out before Islam tended to be more towards political reasons not based on love, impressed because of the power factor so that at that time men could have more than one wife, dozens or even unlimited. The culture of marriage for men who have more than one wife is known as polygamy. Historically, the culture of pre-Islamic polygamy was carried out by ancient civilizations so that the Arabian peninsula, especially the Middle East, was not the main propagator of the polygamous tradition, which is often embedded. Therefore, one of the prominent scholars, namely KH. Husain Muhammad described in his writings that the tradition of polygamy was not a tradition that originated in Islam. Formulation of the problem of how to analyze polygamy related to non-Islamic traditions according to KH. Husein Muhammad and why KH. Husein Muhammad is of the view that polygamy is not an Islamic tradition? The research method used is qualitative research of the type of literature study, the approach used is a historical approach related to Islamic studies, this research is descriptive-analytical with the object of research being polygamy not Islamic tradition. The research results conclude that the culture of polygamy didn’t originate from Islam, because pre-Islamic polygamy in practice seemed misogynistic and tended to dehumanize after Islam arrived. Polygamy improved this situation with the main principles of justice and prioritizing women's rights.